Peran Pusat Kegiatan Belajar Masyarakat (PKBM) Dalam Meningkatkan Kelulusan Anak Putus Sekolah di Kabupaten Belu - Charlos Junior Rebong B.L Paha; Nursalam; Rowland A. Benyamin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Non-formal education, particularly through Community Learning Centers (PKBM), plays a strategic role in improving graduation rates among school dropouts in Belu Regency. PKBM provides equivalency education through packages A, B, and C, as well as skills programs for communities unable to access formal education. This study aims to analyze the role of PKBM in reducing dropout rates and improving student graduation. Through a qualitative approach and case study in two PKBMs, namely PKBM Deflobamora Atambua (urban) and PKBM Brithany Cendana Timur (rural), it was found that PKBM employs holistic, integrative, and flexible strategies tailored to the needs of students, both in terms of curriculum and learning time. Collaboration between PKBM, local government, and communities also plays a key role in the success of the program. However, PKBM still faces challenges such as limited human resources, funding, and facilities. Nevertheless, PKBM has achieved a high graduation rate (90-100%) in recent years, especially in package C, with a learning approach based on practice and technology. This study recommends strengthening PKBM capacity and expanding service coverage to rural areas.